Identification of an Isoflavonoid Transporter Required for the Nodule Establishment of the Rhizobium-Fabaceae Symbiotic Interaction - Biała-Leonhard, Wanda; Zanin, Laura; Gottardi, Stefano; de Brito Francisco, Rita; Venuti, Silvia; Valentinuzzi, Fabio; Mimmo, Tanja; Cesco, Stefano; Bassin, Barbara; Martinoia, Enrico; Pinton, Roberto; Jasiński, Michał; et al. (Frontiers in Plant Science, 2021)
Nitrogen (N) as well as Phosphorus (P) are key nutrients determining crop productivity. Legumes have developed strategies to overcome nutrient limitation by e.g., forming a symbiotic relationship with N-fixing rhizobia and the release of P-mobilizing exudates and are thus able to grow without supply of N or P fertilizers. The legume-rhizobial symbiosis starts with root release of isoflavonoids, that act as signaling molecules perceived by compatible bacteria. Subsequently, bacteria release nod factors, which induce signaling cascades allowing the formation of functional N-fixing nodules. We report here the identification and functional characterization of a plasma membrane-localized MATE-type transporter (LaMATE2) involved in the release of genistein from white lupin roots. The LaMATE2 expression in the root is upregulated under N deficiency as well as low phosphate availability, two nutritional deficiencies that induce the release of this isoflavonoid. LaMATE2 silencing reduced genistein efflux and even more the formation of symbiotic nodules, supporting the crucial role of LaMATE2 in isoflavonoid release and nodulation. Furthermore, silencing of LaMATE2 limited the P-solubilization activity of lupin root exudates. Transport assays in yeast vesicles demonstrated that LaMATE2 acts as a proton-driven isoflavonoid transporter.